Delayed onset muscle soreness: No pain, no gain? The truth behind this adage - Phathokuhle C. Zondi; D. C. Janse van Rensburg; C. C. Grant; A. Jansen van Rensburg (South African Family Practice)
The purpose of this article is to provide brief insight into delayed onset muscle soreness (DOMS), a phenomenon that is often experienced by recreational and elite athletes. The negative implications of DOMS include pain, decreased motivation to continue training, and decreased performance. While performance issues may be more relevant to the elite athlete, pain and decreased motivation are particularly relevant to recreational athletes wishing to sustain a regular level of physical activity. The article is aimed at general practitioners (GPs) who may encounter athletes presenting with DOMS, and who will benefit from understanding the proposed mechanisms, signs and symptoms of the condition. Numerous researchers have hypothesised that certain interventions may prevent or minimise the symptoms thereof, and all GPs could benefit from understanding the available options for athletes, and the scientific evidence that supports these options.